Safety and Effectiveness of Direct Oral Anticoagulants vs. Warfarin in Patients With Atrial Fibrillation and Endoscopy-Diagnosed Peptic Ulcer - Wang, Chun-Li; Huang, Chien-Hao; Wu, Victor Chien-Chia; Huang, Ya-Chi; Wang, Hsiang-Sheng; Kuo, Chang-Fu; Chu, Pao-Hsien; Wen, Ming-Shien; Chen, Ying-Jen; Huang, Yu-Tung; Chang, Shang-Hung (Frontiers in Cardiovascular Medicine, 2021)
Background: Patients with active peptic ulcer (PU) were excluded from direct oral anticoagulant (DOAC) trials for stroke prevention in patients with atrial fibrillation (AF). This study evaluated the safety and effectiveness of DOACs in AF patients with active, inactive and no peptic ulcer (PU). Methods: This study accessed electronic medical records from January 1, 2009 to May 31, 2019 at a multi-center healthcare provider in Taiwan and involved 2,955 AF patients who had undergone esophagogastroduodenoscopy ≤1 year before anticoagulation. Subjects were classified into 3 groups: active (n = 237), inactive (n = 828) and no-PU (n = 1,890) groups. We compared the risks of major bleeding, gastrointestinal bleeding, and ischemic stroke/systemic embolism (IS/SE) between DOACs and warfarin among the 3 groups. Results: In the active PU group, there were no significant differences in the risks of major bleeding [hazard ratio (HR) = 0.65, 95% confidence interval (CI) 0.08–4.98, p = 0.676], gastrointestinal bleeding (HR = 0.65, 95% CI 0.08–4.98, p = 0.676) and IS/SE (HR = 2.58; 95% CI 0.53–12.70, p = 0.243) between DOAC and warfarin (as the reference). In the inactive PU group, there were no significant differences in the risks of major bleeding (HR = 0.36, 95% CI 0.09–1.39, p = 0.138), gastrointestinal bleeding (HR = 0.21, 95% CI 0.02–1.80, p = 0.153), and IS/SE (HR = 1.04, 95% CI 0.39–2.82, p = 0.934) between DOAC and warfarin (as the reference). In the no-PU group, DOACs were associated with lower risk of major bleeding (HR = 0.26, 95% CI 0.12–0.53, p <0.001), gastrointestinal bleeding (HR = 0.25, 95% CI 0.01–0.59, p = 0.002), and similar risk of IS/SE (HR = 0.92, 95% CI 0.55–1.54, p = 0.757) compared to warfarin. Conclusions: DOACs were as effective as warfarin in preventing IS/SE irrespective of PU status and safer than warfarin in reducing major bleeding in the no-PU group. In patients with active or inactive PUs, DOAC and warfarin were not significantly different in their effects on major bleeding or gastrointestinal bleeding.